UNLOCKING THE INTRIGUING DERMOSCOPIC INSIGHTS INTO ACUTE CUTANEOUS LUPUS ERYTHEMATOSUS: A RETROSPECTIVE STUDY. - Hussain, Seeba (Student's Journal of Health Research Africa, 2024)
Background Acute Cutaneous Lupus Erythematosus is a significant manifestation of systemic lupus erythematosus (SLE), characterized by various dermatological symptoms. Dermoscopy has emerged as a valuable tool in the assessment of skin lesions, providing insights into the microvascular and morphological changes associated with ACLE. The study investigated and characterized the dermatoscopic features of acute cutaneous lupus erythematosus, aiming to enhance diagnostic accuracy and provide valuable insights into this condition. Methods Retrospective study aimed to investigate the dermatoscopic features of ACLE and their associations with clinical manifestations. Sixty patients diagnosed with ACLE, meeting the Systemic Lupus International Collaborating Clinics criteria for SLE, were included. A dermoscopic examination was conducted to identify characteristic features, and statistical analysis was performed to assess associations between dermatoscopic findings and clinical characteristics. Results In a study of 60 ACLE patients, dermatoscopic analysis revealed key features: scale crust in 80%, follicular plugs in 70%, erythema in all, dotted vessels in 60%, and linear vessels in 45%. Scale crust strongly correlated with malar rash, and follicular plugs with photosensitivity and oral ulcers, highlighting the diagnostic relevance of these dermatoscopic signs in ACLE. Conclusion The study highlights the diagnostic and prognostic implications of dermoscopy in ACLE, emphasizing its role in enhancing diagnostic accuracy and guiding personalized treatment strategies. Integration of dermoscopy into clinical practice can improve the understanding and management of ACLE, leading to better patient outcomes. Recommendations Dermoscopic examination should be routinely performed in patients with suspected or confirmed ACLE to facilitate early diagnosis and monitoring of disease activity. Training in dermoscopy for dermatologists and rheumatologists is recommended to enhance proficiency in recognizing and interpreting dermatoscopic features associated with ACLE. Further research is needed to validate the diagnostic utility of dermoscopy in larger patient cohorts and to explore additional dermatoscopic features that may aid in the management of ACLE.